On a Subclass of Harmonic Convex Functions of Complex Order - N. Magesh; S. Mayilvaganan (International Journal of Mathematics and Mathematical Sciences)
We introduce and study a subclass of harmonic convex functions of complex order. Coefficient bounds, extreme points, distortion bounds, convolution conditions, and convex combination are determined for functions in this class. Further, we obtain the closure property of this class under integral operator.